Visual Identity in the Digital Era: Decoding the Adaptation of Brands in the Digital Environment. - Martínez Sánchez, María Eugenia; Laureckis Molla, María Eugenia; Buil López-Menchero, Tamar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Corporate Visual Identity (CVI) integrates key elements such as logo, colour and typography, fundamental for brand identification and positioning. This study analyses the logos of the top 100 global brands (Interbrand 2024), through a systematic analysis of the visual elements: composition, symbol, colour, typography and their consistency on platforms such as websites and Instagram. The study evidences the adaptability and consistency of CVI in different digital contexts as pillars in strategic brand management. The research furthers the theoretical contribution in this area by providing a validated scalable model for future research and provides insights as a practical contribution.